LAPORAN KEUANGAN ( SAK ETAP UMKM) MENGGUNAKAN SOFTWARE AKUNTANSI MANAGER (STUDI KASUS PT. PLASTIC COLOR TECHNOLOGY) - Suhartono; Murifal, Badar; Riezky Pahlevi, Raden Mohammad; Kuspriyono, Taat (Fundamental Management Journal, 2020)
In the current millennial era, the speed and accuracy of data as information is needed by various parties, especially managers. Likewise, financial information data that must be presented effectively and efficiently. The speed and accuracy of the presentation of financial data, will greatly help management and other parties in making decisions. Manager accounting software has a very important role and is very helpful for managers in their daily operations. Thisresearch isto findout howto make financial reports at SMEs. The results showed that the manager's accounting software really helped MSMEs in making their financial reports so that they were more accountable. Keywords:Financial Report, Accounting Software Manager